Model Pembinaan Kesehatan Mental Anak dalam Pendidikan Islam (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Mental health construction of the child has vital importance to receive attention. Islamic education offers the solution of the child’s health mental construction conception. Islamic education instructs the student to conduct the construction and development of fitrah with all its potency and eliminate the expanding of negative potency. Construction and development of child’s fitrah with all its potency is believed will make healthy to child’s soul, while model that Islamic education give in this case is with the introduction of values of tauhid and behavior. The introduction of these values can bring about harmonious order in child self as one of the characteristic of mental health.